Ukuran Perusahaan, Likuiditas, Leverage Terhadap Agresivitas Pajak: Profitabilitas Sebagai Moderasi - Monica Sihol Marito Boru Malau (Yayasan Literasi Ilmiah Indonesia, 2021)
Purpose: This study aims to prove the effect of firm size, liquidity, leverage and tax aggressiveness: and the moderating role of profitability Method: the sample used in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2016-2019 and produces 56 sampel data. The testing of this research was conducted using regression analysis and the Moderated regression Analysis (MRA) test. Finding: The findings in this study that firm size has no effect on tax aggressiveness,the liquidity variable has a positive effect on tax aggressiveness, leverage variable has a negative effect on tax aggressiveness. In this study it was found that profitability can moderate firm size on tax aggressiveness, profitability cannot moderate the effect of liquidity on tax aggressiveness, and profitability cannot moderate the effect of leverage on tax aggressiveness. Novelty: the difference between this research and previous research is that this research tries to integrate several topics regarding the tax aggressiveness variable which is influenced by three variables, namely firm size, liquidity, leverage by using the moderating variable of profitability.